Synthesis and characterization of thermosensitive macroporous hydrogels for controlled drug delivery applications - Setiyorini, Yuli (Curtin University, 2010)
The purpose of this research was to synthesize novel macroporous thermosensitive hydrogels and to characterise the produced hydrogel materials for controlled drug delivery applications.Twelve hydrogel polymers were synthesized based on the homo-, co- and/or ter-polymers of N-isopropylacrylamide (NIPAAm), 2-hydroxyethyl methacrylate (HEMA) and ethyl methacrylates (EMA). The polymers were produced in the presence of varying amounts of water so as to generate porous structures of the hydrogels through a phase separation polymerization process. N, N’-methylenebisacrylamide (mBAAm) was used as a crosslinking agent and ammonium persulfate (APS) was used an initiator.The morphology of these hydrogels was examined using scanning electron microscopy (SEM). The porous structure of the hydrogels was future evaluated by the polymer volume fraction at the equilibrium state at various temperatures. The swelling properties of hydrogels were also studied. These include the equilibrium swelling ratio (ESR) and the normalised volume change at different temperatures, the swelling kinetics, and the deswelling kinetics.Based on the porosities and the swelling properties, their responsiveness to the temperature changes, nine hydrogels were selected for the assessment of drug loading capacity and drug diffusion properties using a conventional anti-inflammatory drug, predinisolone 21-hemisuccinate sodium salt. The influence of temperature, porosity and drug concentrations on the drug loading capacity and diffusion kinetics was also investigated.